1993
DOI: 10.1093/protein/6.4.341
|View full text |Cite
|
Sign up to set email alerts
|

The sequence and X-ray structure of the trypsin from Fusarium oxysporum

Abstract: The trypsin from Fusarium oxysporum is equally homologous to trypsins from Streptomyces griseus, Streptomyces erythraeus and to bovine trypsin. A DFP (diisopropylfluorophosphate) inhibited form of the enzyme has been crystallized from 1.4 M Na2SO4, buffered with citrate at pH 5.0-5.5. The crystals belong to space group P2(1) with cell parameters a = 33.43 A, b = 67.65 A, c = 39.85 A and beta = 107.6 degrees. There is one protein molecule in the asymmetric unit. X-ray diffraction data to a resolution of 1.8 A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 3 publications
1
28
0
Order By: Relevance
“…The closure abrogates Na ϩ binding, but isolates D189 from the apparently detrimental effects of a three-way channel shaped as in the Y225I mutant of thrombin. This correlation is reinforced by the crystal structure of the trypsin from Fusarium oxysporum (30), carrying Ser at position 225. In this structure, the carbonyl O atom of residue 224 is oriented as in the proteases with P225 (6) and the channel is shaped as in the Y225P mutant of thrombin.…”
Section: Resultsmentioning
confidence: 92%
“…The closure abrogates Na ϩ binding, but isolates D189 from the apparently detrimental effects of a three-way channel shaped as in the Y225I mutant of thrombin. This correlation is reinforced by the crystal structure of the trypsin from Fusarium oxysporum (30), carrying Ser at position 225. In this structure, the carbonyl O atom of residue 224 is oriented as in the proteases with P225 (6) and the channel is shaped as in the Y225P mutant of thrombin.…”
Section: Resultsmentioning
confidence: 92%
“…Crystals were grown as described elsewhere (15), with the pH lowered to 5.0 instead of 6.0 using 100 mM sodium citrate buffer. A combination of streak seeding and macroseeding was applied to initiate nucleation.…”
Section: Methodsmentioning
confidence: 99%
“…However, examination of all available data bases, including those of the most gene-rich mitochondrial DNA known (62 protein-encoding genes in Reclinomonas americana) (33), the Rickettsia genome, the Rhodobacter (free living ␣-proteobacteria) genome, the Bacillus subtilis (grampositive bacteria) genome, and various archaeobacterium genomes revealed no non-actinomycete eubacterial or archaeobacterium genes that could be paralogous to the metallocarboxypeptidase (7), chymotrypsins, and trypsins found in actinomycetes and eukaryotes. The argument of Rypniewski et al (5,6) that animal, fungal, and Streptomyces trypsins are derived from gene divergence predating the prokaryote/eukaryote split does not explain the patchy and very narrow distribution of these enzymes among fungi and bacteria. Plant and insect pathogenic members of the Ascomycotina and actinomycete bacteria are the only known microbial sources of S1 trypsins.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining sequence data from a trypsin from a lower eukaryote, the fungus Fusarium oxysporum, made it possible to reassess the relationship between the microbial and mammalian trypsins. Finding that the fungal sequence falls between the two classes of organisms, Rypniewski et al (5,6) suggested that no interspecies gene transfer is necessary to explain the homology between trypsins and posited a continuos evolutionary divergence from a common ancestor of prokaryotes and eukaryotes. However, recently we cloned a class of metallocarboxypeptidase from Metarhizium anisopliae, not found previously in fungi, that also fell between Streptomyces and animal sequences and had only distant homologs in other bacteria (7).…”
mentioning
confidence: 99%